PENGARUH KEMAMPUAN PENGGUNAAN ALAT UKUR LISTRIK TERHADAP KEMAMPUAN PSIKOMOTORIK MAHASISWA PADA PRAKTIKUM ELEKTRONIKA DASAR - Safriana Safriana (Jurnal Dedikasi Pendidikan, 2017)
Electrical measuring instruments and basic electronics laboratories are two things that can not be separated. Mastery using electric measuring devices will affect the practical activities and values obtained from the lab. This research is motivated by the still low mastery of electric appliance using FKIP Unimal students. In fact, almost all of the basic electronics lab activities use electrical measuring instruments to determine the behavior of electronics circuits. This study aims to determine how much influence the ability of the use of electrical measuring instruments to psychomotor ability of students on basic electronics laboratory. Population and sample are all students of FKIP Unimal in year 2015 is totaling 60 people. Sampling technique using non-probability sampling technique. The data collection tool used in this research is rubric or observation sheet which has been tested its validity and reliability. The research analysis used correlation analysis, simple regression and t test. Based on the results of statistical tests obtained significance value paired sample t-test of 0.000 with a value of t arithmetic 10,346. Because significance less than 0.005 so it can be said that there is a positive effect and significant ability of electrical measuring instruments to the psychomotor ability of students on basic electronics practice.